The anatomy of ‘So-called Food-Fraud Scandals’ in the UK 1970–2018: developing a contextualised understanding - Smith, Robert (Crime, law and social change, 2022)
In the last four decades, the food industry in the United Kingdom has been subject to a considerable number of so-called "food-fraud scandals". These incidents mainly relate to actual, or alleged fraudulent activity which has resulted in public outcries about the criminality and industry malpractices which may underpin them. An analysis of these ‘scandals’ reveals that there is a ‘scripted’ nature to both their revelation and resolution, which can be modelled to help better understand how to investigate and theorise these incidents in context. This approach enables a better, more nuanced understanding of how to read the signs that link an incident to a given modus operandi and as a consequence enables relevant actors to take more appropriate and timely responsive actions, especially in the midst of a scandal narrative. Eight food related incidents are scrutinised, some termed scandals, and others that whilst receiving local or national media attention were not framed in the associated discourse as ‘being scandals.’ These case studies demonstrate the contextualised anatomies of each specific scandal to then identify the associated scripted themes and responses. The framework developed as an output from this research is of value in recognising the stages and nuances of a food-fraud scandal narrative.